2018
DOI: 10.26480/mjsa.01.2018.19.28
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of the Efficiency and Productivity of Selected Food Processing Industries in Malaysia

Abstract: The purpose of this study is to evaluate the performance and change in the technical as well as technological efficiency in the total factor productivity of the 34 food processing industries in Malaysia, and to investigate the changes in their efficiency from 2009 to 2010 by applying two recent methods of data analysis, namely order-m and Malmquist productivity index. The results show that almost all industries have experienced an efficient technological contribution in their respective production functions, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…The main results showed that the growth of TFP of food processing enterprises in Malaysia is a change of technical progress, but LSEs can also improve TFP growth by promoting production frontier. Additionally in the context of Malaysia, Munshi Naser et al [23] applied order-m and Malmquist index to explore total factor productivity change in 34 food processing industries using data from 2009-2010. The results demonstrated that almost all industries go through effective technical contribution in their respective production functions, but the technical progress of the organic components of each industry varies greatly.…”
Section: Literature Review On Malmquist Total Factor Productivity Indexmentioning
confidence: 99%
“…The main results showed that the growth of TFP of food processing enterprises in Malaysia is a change of technical progress, but LSEs can also improve TFP growth by promoting production frontier. Additionally in the context of Malaysia, Munshi Naser et al [23] applied order-m and Malmquist index to explore total factor productivity change in 34 food processing industries using data from 2009-2010. The results demonstrated that almost all industries go through effective technical contribution in their respective production functions, but the technical progress of the organic components of each industry varies greatly.…”
Section: Literature Review On Malmquist Total Factor Productivity Indexmentioning
confidence: 99%
“…Responsiveness is a key factor which influences speed; and the food industry in particular is an example of this "off-the-shelf" responsiveness characteristic (Kritchanchai, 2004). If a country cannot stock its produced food for a longer period of time, the possibilities of exporting such foods become limited to fresh foods only which are associated with higher costs (Afzal, Lawrey, Anaholy, & Gope, 2018). In other words, the agriculture and food industries are distinctive in the sense that the produce of these industries have a very limited shelf life.…”
Section: Introductionmentioning
confidence: 99%
“…El índice de Malmquist a nivel internacional es ampliamente utilizado en las mediciones de productividad y en la agroindustria (Headey et al, 2010), Baliyan et al, 2015;Tan et al, 2017;Afzal, et al, 2018;Liu et al,2018;Pérez et al, 2019;Kryszak, et al, 2021;Aslam et al, 2021;Shahraki, & Aliahmadi, 2021;Kaur, 2021;Wang et al, 2020;Tan et al,, 2020 Baliyan et al, (2015) examinaron el crecimiento de la productividad total de los factores en la industria de procesamiento de alimentos de la India, encontrando que durante las últimas tres décadas, todos los segmentos de la industria de procesamiento de alimentos mejoraron la productividad (TFP); no obstante los productos cárnicos, pesqueros, frutas y verduras, y aceites y las grasas cayeron en TFP. En el estudio se enfatiza la necesidad de identificar e implementar fuentes sostenibles de crecimiento de la productividad en el sector agrícola y la industria de procesamiento de alimentos de la India, indicando que la tecnología es la clave para mejorar el crecimiento y la eficiencia en el sector.…”
Section: Estudios De Productividad En La Agroindustriaunclassified